The determination of benzalkonium chloride in eye drops - Blazheyevskiy Mykola; Koval'ska Olena
ABSTRACT Aim: A novel sensitive kinetic photometric method for the benzalkonium chloride determination has been developed. Materials and method: The method is based on the ability to inhibit the reaction of acetylcholine hydrolysis by cholinesterase. The reaction rate is evaluated by the non-hydrolysed acetylcholine residue, which is determined by the amount of Peracetic acid, produced during the interaction with the excess of solution hydrogen peroxide . Indicator reaction is an interaction of p-phenetidine with Peracetic acid that leads to the formation of 4,4'-azoxyphenetole with λmax = 358 nm (log10 ε =4.2). Results: The conditions affecting the reaction (reagents concentration, pH, order of addition of reagents, stability in time) have been optimized. The linear dependence has been obeyed in the range of (1.4 to 8.4)·10-6 of benzalkonium chloride with correlation coefficient of 0.999. The assay limit of quantitation (20 % of the inhibition degree) has been 1.9·10-6 mol L-1. Conclusion: The proposed method has been successfully applied to the analysis for eye drops and allowed to confirm accuracy and reliability of the results obtained.